Aktivitas Antioksidan Teh Kombinasi Daun Katuk Dan Daun Kelor Dengan Variasi Suhu Pengeringan - Sayekti, Erviana Duwi; , Dra. Aminah Asngad, M. Si; , Siti Chalimah, Dr, MPd (2016)
Combination tea katuk leaves and moringa leaves is one innovation and the optimization utilization of katuk plants and moringa plants. Katuk leaves and moringa leaves it contains antioxsidant compounds such as tannins, flavonoids, alkaloids, triterpenes, essentials oil and saponins. The purpose of this study to determine the antioxidant activity and organoleptic quality of the combination tea of katuk leaves and moringa leaves with drying temperature variations. The research method completely randomized design (CRD) with two factors , there are factor 1 : temperature variation 45°C (T1), 50°C (T2), 55°C (T3) and factor 2 : concrentation variation of katuk leaves and moringa leaves 1:1 (L1), 2:1 (L2), 1:2 (L3). The result showed that there were differences in the results of antioxsidants of the combination tea of katuk leaves and moringa leaves. The highest antioxidant activity on T3L3 (temperature 55ºC with katuk leaves 0,7 g : moringa leaves 1,3 g) is 74,9% and the lowest antioxidant activity on T1L2 (temperature 45ºC with katuk leaves 1,3 g : moringa leaves 0,7g ) is 30,6%. The combination tea of katuk leaves and moringa leaves with treatment T2L1, T3L1, T2L2, T2L3, dan T3L3 have dark yellow, bland taste, rather somewhat unpleasant flavor, and like acceptance. Keyword : Tea, katuk leaves, moringa leaves, antioxidant activity.